Examining the value of after-sales services through the lens of service-dominant logic :|a conservation-of-resources-theory interpretation - Kuzgun, Ebru. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The current study investigates the customers’ after-sales service (AS-S) experiences with a framework based on service-dominant logic that involves both value co creation and co-destruction elements. The main constructs that are investigated as a means to comprehend customers’ AS-S experiences are contemplated upon the conservation of resources theory. Accordingly, the study develops and proposes constructs of primary resource loss (i.e. losses of value-in-exchange, value-in-use, and value-context), resource conservation effort (i.e. process, mental, and legal/punitive efforts), secondary resource loss (time, self-esteem, consumer-rights, and material/financial losses), and finally secondary resource gain (convenience, support, self-esteem, and material/financial gains) that emerge in consumers’ AS-S experiences. The purpose of this study is to understand how these constructs are related to each other and to the customers’ service satisfaction in shaping their overall AS-S experiences. Two conceptual models are proposed with an intention to devote separate focus on co-creative after-sales service experiences that results in secondary consumer gains and on co-destructive after-sales service experiences that ends up with secondary consumer losses. The proposed models are empirically tested with data from 422 consumers in Turkey. The hypotheses are tested with the utilization of Structural Equation Modelling (SEM) in SPSS AMOS. The results indicate different paths that after-sales service specific secondary losses and secondary gains would follow which eventually leads to satisfaction (for co-creative service settings) and dissatisfaction (for-co-destructive service settings).
Keywords: Consumer satisfaction.; Customer services.